Vietnamese Women’s Responses to Domestic Violence in South Korea (Asian Journal of Social Science Studies, 2018)
The purpose of this study is to explore Vietnamese women’s responses to domestic violence in South Korea. Based on in-depth interviews with 22 Vietnamese women who marry Korean men, six strategies to cope with domestic violence are identified: enduring, escaping, confronting, negotiating, getting help from informal networks, and seeking assistance from formal sources. This study presents that informal social networks are critical in the process of help seeking for abused Vietnamese women.